Ustadz as agents of religious moderation in islamic boarding schools: Concepts, strategies, and impacts at pesantren mta, karanganyar - Muin Abdullah; Annafi’ Nurul’Ilmi Azizah; Mohammed Hafiz Ali Wafa; Habib Assalam (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This study examines the role of ustadz as agents of religious moderation at the Majelis Tafsir Al-Qur’an (MTA) Islamic Boarding School in Karanganyar, Central Java, through a qualitative case study involving 12 informants using interviews, observations, and documentation. The findings indicate that educational background and preaching experience influence the ustadz’s understanding and strategies in internalizing moderation, whether through sermons, discussions, exemplary conduct, or non-formal activities, although consistency remains uneven. The ustadz play a role in fostering tolerance and social harmony, with positive impacts on students’ mindsets, making them more critical, inclusive, and tolerant, despite some still perceiving moderation as a weakening of principles. Challenges include student resistance, limited ustadz capacity, and the influence of digital media, while opportunities involve media literacy, inter-community activities, and internal policies. The success of religious moderation depends on curriculum integration, role modeling, and sustainable social guidance, which can be replicated in other Islamic boarding schools.